Analysis of Audience Receptions of Jusuf Hamka's Simple Style in Denny Sumargo's Podcast "Toll Conglomerate ⁉ I Want To Be a Really Rich Person, Not Just To Look Rich ‼" - Naufal, Muhammad Raihan (The Indonesian Journal of Communication Studies, 2024)
This research analyzes the public's reception of Jusuf Hamka's simple style in the podcast "Toll Conglomerate ⁉ I Want to Become a Real Rich Person, Not Just Look Rich ‼" by Denny Sumargo. The research method uses a qualitative approach with content analysis techniques to understand the audience's responses, perceptions, and interpretations of the content presented. Hopefully, this Research will provide deeper insight into how Jusuf Hamka's simple style in the context of a podcast is understood and absorbed by the audience. These findings can provide an important contribution to understanding public communication, especially in the context of digital media such as podcasts, and provide new insights regarding people's aspirations and perceptions of the financial security theme presented in the podcast. The author uses a reception analysis method with a qualitative approach; researchers here use several research concepts, namely, new media, communication style, reception, audience, and simple style. The research results indicate that all informants have a uniform view, creating a dominant hegemony in the reception of Jusuf Hamka's simple style. The implications of these findings can be used as a basis for content creators and media to understand audience preferences and improve the quality of communication in delivering straightforward, everyday content.